Gambaran Pelaksanaan Pelatihan Hypnoparenting untuk Mengatasi Masalah Perkembangan Anak Balita - Heny Noor Wijayanti; Yana Luthfiyati; Nabila Apriliani (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2021)
Background: During the toddler years, there is a very rapid growth and development process, both physical, psychomotor, mental and social growth. The first five years of life are a golden period for the environment and will be the basis for the nation's future generations. Almost 90% of children's problems are caused by parents' mistakes or ignorance of how to communicate and convey good values ​​to the child. Hypnoparenting techniques are ways that parents can do in overcoming various kinds of problems that make children. Purpose: this activity is to apply good parenting with hypnoparenting so that children's development can be even better. Methods: the implementation of the activity consists of 2 stages of training on hypnoparenting, and evaluation of hypnoparenting practices by the child's parents. Results of Community Service: the initial results were given a questionnaire about hypnoparenting, some of the respondents who had never known about hypnoparenting were 7 people (70%), parents who were enthusiastic in the training and application of hypnoparenting. Conclusion: parents can practice giving their children positive suggestions so that children's development is getting better.